The use of computer technology in the english language classroom in motivating students’ learning in Sekolah Menengah Tengku Bariah Kuala Terengganu / Nor Suriati Othman - Othman, Nor Suriati (2010)
The policy to integrate the usage of Information & Communication Technology (ICT) in education is one innovation of the nation in ‘Vision 2020’. The aim is to make Malaysia a fully developed country by the year 2020. Our former Prime Minister, Datuk Seri Abdullah Ahmad Badawi has addressed that the power of ICT has improved our quality of life whether in the urban or rural area as it has increased our digital literacy rate (Women And Information And Communication Technology (ICT), 2000). The main purpose of setting up of the Malaysia Superhighway Corridor (MSC) and Vision 2020 is to bring Malaysia into becoming technological literate in order to be able to participate in the critical thinking workforce in the global economy of the 21st century (Nor Azilah & Mona, 2005). Vision 2020 and globalization has also brought about many changes and modifications to the Malaysian school curriculum whereby it transformed its educational system from the traditional approach to a more interactive style of teaching. Through the implementation of ICT in the Malaysian’s education system, the Ministry of Education’s (MOE’s) target to educate students in becoming computer literate citizens with critical thinking mind besides positioning ICT as one of the teaching and learning tools (Ministry of Education, 2004). It is reported that our Deputy Prime Ministry, Tan Sri Muhyiddin agrees that the use of ICT in teaching and learning tools can catalyze better education outcomes in the new economy (Bernama, 2010).